PENGARUH MODEL PEMBELAJARAN KOOPERATIF TIPE NUMBERED HEADS TOGETHER (NHT) BERBANTUAN WORDWALL TERHADAP HASIL BELAJAR PENDIDIKAN PANCASILA DI SEKOLAH DASAR - Nurhidayah; Syarif, Irman; Wulandari (STKIP Subang, 2026)
This study aims to determine the effect of implementing the cooperative learning model of the Numbered Heads Together (NHT) type assisted by Wordwall media on students’ learning outcomes in Pancasila Education on the topic